Exploring the Role of Pediatric Neurology in Determinations of Futility, Identifying Vulnerability, and Participating in Shared Decision Making through Case-Based Analysis - Quezada, Julio; Lantos, John D. (Journal of Pediatric Epilepsy, 2020)
It is not uncommon for pediatric neurologists to encounter ethical dilemmas in clinical practice. These dilemmas not only require an exploration of the basic bioethical principles, but also considering that neurological disease can have impact on a person's self-identity. Patients with neurological disease are particularly vulnerable and at risk of having long-term sequelae of their nervous system and their individual selves. These important considerations can then raise the question of futility of treatment in a setting of uncertainty of outcome. In these complex situations, a pediatric neurologist plays an important role in shared decision making with both families and multidisciplinary teams. In this paper, we explore case-based scenarios that serve to demonstrate the unique character of ethics in neurology and the role of pediatric neurologists in finding solutions that are in a patient's best interest, have a minimal chance of harm, respect a patient's autonomy, and are just and promote justice.
Keywords: ethics in neurology; vulnerability; futility; social determinants of health in neurology